119k views
2 votes
How do I solve this? My math teachers key says that it is 1 but I’m not sure how he got that.

How do I solve this? My math teachers key says that it is 1 but I’m not sure how he-example-1
User DimyG
by
4.9k points

1 Answer

7 votes

Given:


\lim_(x\to-1)(\sqrt[3]{x}-\frac{2}{\sqrt[3]{x}})^5

You need to substitute this value of "x" into the expression inside the parentheses, in order to evaluate the limit:


x=-1

Then:


\lim_(x\to-1)(\sqrt[3]{-1}-\frac{2}{\sqrt[3]{-1}})^5

By definition:


\sqrt[3]{-1}=-1

User Barka
by
5.6k points